PERANCANGAN KAMPANYE SOCIAL TENTANG PENGAWASAN GADGET PADA ANAK UNTUK ORANG TUA - Widiya Lestari Harahap; Dicky Darmawan (Universitas Budi Luhur, 2024)
The development of science and technology brings changes to almost the entire order of human life. The use of gadgets or smartphones that almost everyone has today. The negative impact of using children's gadgets without parental supervision includes children will be irritable, even disobedient, even imitating behavior from what they watch from these gadgets besides that excessive use of gadgets without parental supervision can have a negative impact on children's development. Therefore, a media is needed that is able to convey the message to parents that children who are given gadgets without supervision will have a negative impact on their development. The campaign